DEVELOPMENT OF SOUR-MILK HEALTHY BEVERAGES WITH THE USE OF NATURAL HERBAL NANOADDITIVES - R. Pavlyuk (Harčova Nauka ì Tehnologìâ, 2019)
Technologies of healthfull products - bioyogurts with unique characteristics have been developed. The new products are characterized by a high content of naturally occurring biologically active substances - phytocomponents of fruits and vegetables (carrots, lemons with zest, apples, Jerusalem artichoke), in particular, β-carotene, phenolic compounds, tannins, ascorbic acid, ie substances having antioxidants. Besides, they have a high content of prebiotic substances - soluble pectic substances, cellulose, inulin and proteins. Recent biogurts play the role of natural thickeners and structure-forming agents. This makes it possible to eliminate the need for the use in the production of bio yoghurt food additives and synthetic additives. Technologies for making bio yoghurts are based on the use of nanosized cryo-additives from nanosize with the record content of biologically active substances (BAS), whose mass fraction in cryo-additives is 2.5 - 5.0 times greater than the original fresh cheese. Obtaining the latter is based on the complex action on the raw materials of cryogenic "shock" freezing with the use of liquid and gaseous nitrogen and cryodestruction with fine grinding. When making bioyoghurts, cryoadditives act as natural enrichment agents, structure-forming agents, texture stabilizers and dyes. In addition, phytoextracts from natural spices and medicinal herbs (echinacea, coriander, burkun, oregano) are included in the formulations for the enrichment of the BAS and for longer shelf life of new bio yoghurts. Whey was used as the basis for the production of bio yoghurts. New types of bio yoghurts in terms of the content of BAS exceed the known analogues and have 2 times longer shelf life (than control samples). Technological modes of production of bioyoghurts on bench semi-industrial equipment have been worked out. New yoghurts are recommended for introduction into production at large food enterprises, in establishments of restaurant business, for individual food.